One- and two-electron reduction of triarylborane-based helical donor–acceptor compounds. Issue 35 (11th August 2021) - Jia, Xiangqing; Nitsch, Jörn; Wu, Zhu; Friedrich, Alexandra; Krebs, Johannes; Krummenacher, Ivo; Fantuzzi, Felipe; Braunschweig, Holger; Moos, Michael; Lambert, Christoph; Engels, Bernd; Marder, Todd B.
Abstract : Stepwise chemical reduction of D–π–A triarylborane-based helicenes gives the corresponding monoanions and dianions with delocalized unpaired electrons. The structures were confirmed by single crystal X-ray diffraction. Abstract : One-electron chemical reduction of 10-(dimesitylboryl)- N, N -di- p -tolylbenzo[ c ]phenanthrene-4-amine (3-B(Mes)2 -[4]helix-9-N( p -Tol)2 ) 1 and 13-(dimesitylboryl)- N, N -di- p -tolyldibenzo[ c, g ]phenanthrene-8-amine (3-B(Mes)2 -[5]helix-12-N( p -Tol)2 ) 2 gives rise to monoanions with extensive delocalization over the annulated helicene rings and the boron p z orbital. Two-electron chemical reduction of 1 and 2 produces open-shell biradicaloid dianions with temperature-dependent population of the triplet states due to small singlet-triplet gaps. These results have been confirmed by single-crystal X-ray diffraction, EPR and UV/vis-NIR spectroscopy, and DFT calculations.